HUBUNGAN ASUPAN MAGNESIUM DAN VITAMIN C DENGAN GULA DARAH SEWAKTU PASIEN DM TIPE 2 DI RUANGAN RAWAT INAP RSUD. PROF. DR. W. Z. JOHANNES KUPANG - angelita alexandrina; Anak Agung Ayu Mirah Adi; Regina Maria Boro (Poltekkes Kemenkes Kupang, 2026)
Type 2 diabetes mellitus occurs when the body can no longer produce sufficient insulin or is unable to use insulin effectively. According to SKI 2023, the prevalence of type 2 diabetes among individuals aged ≥15 years reached 50.2%, while East Nusa Tenggara Province reported a prevalence of 45.9% in the same year. Medical record data from Prof. Dr. W. Z. Johannes Kupang Regional General Hospital indicated that there were 797 cases of type 2 diabetes mellitus from January to December. This study was conducted to assess the relationship between magnesium and vitamin C intake and random blood glucose levels in patients with type 2 diabetes mellitus. The study employed a descriptive analytical approach with a cross-sectional design, conducted from June 17 to July 17, 2025. Samples were selected using purposive sampling, resulting in 40 respondents who met the inclusion criteria. The variables examined included magnesium intake, vitamin C intake, and random blood glucose levels, all analyzed using the Chi-Square test. The findings revealed that 42.5% of respondents (17 individuals) had deficient magnesium intake. The Chi-Square test produced a p-value of 0.002, indicating a significant association between magnesium intake and random blood glucose levels. Meanwhile, 20 respondents (50%) had deficient vitamin C intake, but the statistical test showed a p-value of 0.184, demonstrating no significant relationship. Additionally, 39 respondents (97.5%) had high random blood glucose levels, with only one respondent (2.5%) falling within the normal category. Overall, the study concludes that magnesium intake is significantly associated with random blood glucose levels, whereas vitamin C intake shows no such association among patients with type 2 diabetes mellitus.